Angiopoietin-2 Is Implicated in the Regulation of Tumor Angiogenesis - Yu, Qin (American Society for Investigative Pathology, 2001)
We addressed the effect of angiopoietin expression on tumor growth and metastasis. Overexpression of angiopoietin-2 (Ang-2) in Lewis lung carcinoma and TA3 mammary carcinoma cells inhibited their ability to form metastatic tumors and prolonged the survival of mice injected with the corresponding transfectants. In contrast, angiopoietin-1 (Ang-1) overexpression had no detectable effect on the ability of either tumor type to disseminate. Tumors derived from Ang-2-overexpressing cells displayed aberrant angiogenic vessels that took the form of vascular cords or aggregated vascular endothelial cells with few associated smooth muscle cells. These vascular cords or aggregates were accompanied by endothelial and tumor cell apoptosis, suggesting that an imbalance in Ang-2 expression with respect to Ang-1 and vascular endothelial growth factor may disrupt angiogenesis and tumor survival in vivo. Our observations suggest that Ang-2 may play an important role in regulating tumor angiogenesis.